The perpetual movements of anaphase - Maiato, H (2010)
One of the most extraordinary events in the lifetime of a cell is the coordinated separation of sister chromatids during cell division. This is truly the essence of the entire mitotic process and the reason for the most profound morphological changes in cytoskeleton and nuclear organization that a cell may ever experience. It all occurs within a very short time window known as “anaphase”, as if the cell had spent the rest of its existence getting ready for this moment in an ultimate act of survival. And there is a good reason for this: no space for mistakes. Problems in the distribution of chromosomes during cell division have been correlated with aneuploidy, a common feature observed in cancers and several birth defects, and the main cause of spontaneous abortion in humans. In this paper we critically review the mechanisms of anaphase chromosome motion that resisted the scrutiny of more than one hundred years of research as part of a tribute to the pioneering work of Miguel Mota.